EKSISTENSI DAN KETUNGGALAN TITIK TETAP BERSAMA DI RUANG METRIK CONE (KERUCUT) UNTUK PASANGAN FUNGSI EKSPANSIF - Indah Saniatur Rohma; Ahmad Khairul Umam (Jurnal Matematika dan Sains (JMS), 2023)
The metric space is one of the most important designs in the field of functional analysis. In 2007 Huang and Zhang introduced the concept of a metric space into a cone metric space. They have proved several fixed point theorems for contraction functions using cone normality. The aim of this study is to examine the singularity of the common fixed points in the cone metric space for pairs of expansive functions. This research was conducted using the literature study method, namely by analyzing and outlining the designs already available in the literature. Furthermore, from this study it can be proven that the onto (surjective) function that satisfies the contractive condition in the cone metric space has a single fixed point together.